2012
DOI: 10.1007/s11418-012-0645-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic effect of α-mangostin

Abstract: Eleven known prenyl xanthones, isolated from the pericarp of Garcinia mangostana, were tested for their ability to inhibit the phosphorylation of kinase domain receptor (KDR) tyrosine kinase. α-Mangostin was found to inhibit phosphorylation of KDR. α-Mangostin also showed to inhibit phosphorylation of the Y1175 residue of KDR (10 μM). This is the first report that α-mangostin inhibited the phosphorylation of KDR tyrosine kinase and also the Y1175 residue of KDR. α-Mangostin also showed inhibitory effects on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
0
15
1
Order By: Relevance
“…It has also been shown that VEGF increases cell proliferation and tube formation through phosphorylation of ERK1/2 in retinal microvascular endothelial cells and in a rat OIR model (Bullard et al, 2003). A recent study reported that α-mangostin treatment of human umbilical vein endothelial cells (HUVEC) inhibited their proliferation, migration and tube formation (Shiozaki et al, 2012). These investigators also reported that α-mangostin treatment prevented ATP-induced phosphorylation of the tyrosine 1175 residue in recombinant VEGFR2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that VEGF increases cell proliferation and tube formation through phosphorylation of ERK1/2 in retinal microvascular endothelial cells and in a rat OIR model (Bullard et al, 2003). A recent study reported that α-mangostin treatment of human umbilical vein endothelial cells (HUVEC) inhibited their proliferation, migration and tube formation (Shiozaki et al, 2012). These investigators also reported that α-mangostin treatment prevented ATP-induced phosphorylation of the tyrosine 1175 residue in recombinant VEGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…α-mangostin is the one of the major biological components of mangosteen. Recently, it has been shown that α-mangostin inhibited growth of umbilical vein endothelial cells and suppressed ATP-induced phosphorylation of recombinant VEGFR2 at Y1175 (Shiozaki et al, 2012). However, the effect of α-mangostin on VEGF signaling and VEGF-induced hyperpermeability and angiogenesis has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Jittiporn et al [102] found that α-MG dramatically and dose dependently suppressed VEGF-induced hyperpermeability, increased proliferation, migration, and tube formation in retinal endothelial cells, and limited vascular sprouting in the ex vivo aortic ring assay through suppressing VEGF-induced phosphorylation of VEGFR2 and ERK1/2 (a major downstream target of VEGFR2). Another study reported on its inhibitory effects on VEGF-induced proliferation, migration, and tubule formation of human umbilical vein endothelial cells [103]. This study also examined site-specific phosphorylation of VEGFR2 and revealed that α-MG inhibited ATP-induced phosphorylation of recombinant VEGFR2 at the Y1175.…”
Section: Suppression Of Angiogenesismentioning
confidence: 82%
“…Human breast cancer MCF-7 cell [94] Inhibition of angiogenic and metastatic progression VEGF expression↓ Breast cancer T47D cells [99] VEGF-A/SDF-1 secretion↓ Activated pancreatic stellate cells [101] VEGFR2↓, EKR1/2↓ Retinal microvascular endothelial cells [102] Phosphorylation of VEGFR2↓ Human umbilical vein endothelial cells [103] MMP-2/MMP-9/NF-κB/Akt1 expression↓ Human melanoma SK-MEL-28 cells [105] MMP-2/NF-κB expression↓, IκBα expression↑ Human squamous cell carcinoma A-431 cells [106] continued…”
Section: Molecular Modeling and Docking Studymentioning
confidence: 99%
“…Mangosteen extracts, including α-mangostin, apparently have somewhat more effective anti-angiogenic properties in vivo in the mammary cancer model used in this study [21,23]; however, the mechanism of angiogenic inhibition by α-mangostin may be related to a reduction in Akt phosphorylation [19][20][21], rather than to antigenantibody interactions; phosphatidylinositol 3-kinase (PI3K) exerts regulatory functions on tumor growth and angiogenesis, as well as on cell proliferation, cell transformation and apoptosis, through downstream targeting of Akt [40]. α-Mangostin inhibited angiogenesis in human umbilical vein endothelial cells and was associated with inhibited phosphorylation of VEGFR2 in vitro [41].…”
Section: Discussionmentioning
confidence: 99%